ORGANIZATIONAL MANAGEMENT FOR THE ARABIC LANGUAGE EDUCATION STUDY PROGRAM AT STIBA AR-RAAYAH - Nidaul Jannah; Nuril Mufidah; Abdul Malik Karim Amrullah; Abdul Halim Muhammad (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2022)
Management has an important role in education to carry out activities and programs, institutions or organizations or any project cannot stand alone without management, Stiba Ar-raayah has developed a curriculum and management that is different from other universities in Indonesia, where students have to live in a dormitory for 5 years to maintain an Arabic environment. This research uses a qualitative descriptive approach and a qualitative approach, namely the latest picture of management for the Arabic Language Education Study Program in stiba Ar-raayah and its organization. structure and look at the principle principles of its organization. This study aims to describe the management of the organization for the PBA study program in stiba Ar-raayah. The results of this study explain that the management for the PBA study program in stiba Ar-raayah in its principle principles can be detailed: the existence of clear objectives in its vision and mission, program planning is assigned to the person in charge of each division at the beginning of each academic year at the work meeting, delegation of authority in writing with an organizational structure, a wide range of control with the presence of subordinates the many, clear and detailed job descriptions, types of line and staff organizations, as well as the presence of a clear organizational structure, this shows that the organization in Stiba ar-raayah is well structured